Fundus autofluorescence features specific for EYS-associated retinitis pigmentosa - Taro Kominami; Tien-En Tan; Hiroaki Ushida; Kanika Jain; Kensuke Goto; Yasmin M. Bylstra; Ai Fujita Sajiki; Ranjana S. Mathur; Junya Ota; Weng Khong Lim; Koji M Nishiguchi; Beau J. Fenner (PLoS ONE, 2025)
Purpose To assess the utility of fundus autofluorescence (FAF) patterns for predicting the EYS genotype in retinitis pigmentosa (RP) patients. Methods This retrospective, multi-institutional study analyzed FAF images from 200 RP patients (74 with EYS and 126 without EYS) from Singapore and Japan. Seven FAF patterns including the infinity sign and a broad banded hyper-autofluorescent leading edge were evaluated for their association with the EYS genotype. Results The infinity sign and broad banded hyperautofluorescent leading edge occurred more frequently in EYS eyes (p = 0.0014 and p = 0.036 respectively). Logistic regression analysis showed that the infinity sign was predictive of EYS (p = 0.003). The combined FAF parameters predicted EYS with a specificity of 95.20%, sensitivity of 25.68% and accuracy of 69.50%, with a cut-off value 0.5 based on the probability of seven FAF parameters. Conclusions In this multinational cohort study of patients with RP, we demonstrated that specific FAF patterns, particularly the infinity sign, have clinical utility in identifying patients with EYS-associated disease. These findings may be useful for clinicians and geneticists when genotyping patients with RP, and may also enhance our understanding of underlying pathophysiology of EYS-associated RP, which is a prevalent cause of RP in Asia and elsewhere.